Ontology-driven and template-based approach for usability requirements elicitation and specification - Too, Chian Wen (2018)
Nowadays, due to the high demand for quality software, the challenges facing by developers to meet the user expectations are increased from time to time. Usability, a quality attribute related to efficiency, effectiveness and satisfaction of the end users to a system has been recognized as one of the significant factors that can influence user preferences and acceptance of software products. However, due to its abstract in characteristic and most of the software developers are lack of sufficient knowledge or expertise about usability issues, usability requirements are always being neglected especially from the early stage of software development. Typically, usability requirements are being specified at the later stage, such as during design, implementation or evaluation. The improper treatment of usability issues always cause the poor quality in software products and can contribute largely to software failure. As a result, it increases the efforts and costs of resolving usability problems after the software implementation and deployment. Therefore, an essential approach for considering and incorporating usability requirements start from the early stage of software development especially during the requirements elicitation became tremendously important. This study attempts to address the issues in improper treatment of usability by proposing a conceptual framework known as Usability Requirements Elicitation and Specification (UReS). The UReS is an ontologydriven and template-based approach mainly used for usability requirements elicitation and specification during the requirements engineering (RE) activities. UReS aims to provide semantic guidance to facilitate the requirement engineer in eliciting the relevant usability features of a domain’s function and specifying the usability requirements. To ensure the sufficient knowledge on usability is provided, a domain ontology which encodes the knowledge about usability features that are relevant to a domain context is designed and acts as the knowledge model in UReS framework during the requirements elicitation activity. Meanwhile, to foster the consistency and clarity of requirements specification, UReS uses a set of predefined boilerplate template to support the process of usability requirements specification. Apart from that, an UReS prototype tool has been developed to support the automation of UReS conceptual framework for facilitating the requirement engineer in performing the requirements elicitation and specification tasks. Furthermore, UReS conceptual framework and the prototype tool are validated using controlled experiment and usability study. The results achieved from the controlled experiment shows that the treatment approach, UReS framework performed well compared to control approach, the manual usability guidelines in terms of the accuracy which measured by correctness and completeness and the number of consistent and unambiguous usability requirements specification generated. In addition, the usability study used to evaluate the user perceptions in terms of the usefulness and usability of UReS prototype tool has received positive feedbacks from the targeted respondents.